PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN KEKERASAN SEKSUAL: STUDI KASUS DI PPA MANADO - Farida Malurung; Basyarudin Basyarudin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the legal protection of child victims of sexual violence in Manado, focusing on a case study at the Integrated Service Center for the Empowerment of Women and Children (PPA). Sexual violence against children is a severe violation that requires comprehensive handling from both legal and social aspects. This research employs an empirical juridical method by reviewing relevant legislation and analyzing data from PPA Manado regarding the handling of child sexual violence cases. The findings indicate that PPA Manado has played a significant role in providing legal, psychological, and social assistance to child victims of sexual violence. However, there are obstacles in law enforcement against perpetrators, such as prolonged legal processes and limited public awareness of children's rights. Moreover, the application of the Child Protection Act and criminal law in sexual violence cases against children in Manado is considered suboptimal, as some victims do not receive timely and adequate justice. This study concludes that legal protection for child victims of sexual violence in Manado needs to be strengthened through improved coordination between PPA, law enforcement agencies, and increased public awareness of the importance of child protection. Recommendations include enhancing the capacity of PPA resources, improving law enforcement mechanisms, and public education to strengthen the prevention of sexual violence against children